Extending Awareness of Open Science via Peers: The ERUA Open Science Ambassador Programme - Sonja N. Kralj; Maximilian Heber; Paulina Helmecke (Liber Quarterly: The Journal of European Research Libraries)
Reaching researchers in terms of Open Science-related matters is a big challenge for Open Science professionals. To encourage peer exchange among researchers working at universities of the European Reform University Alliance (ERUA), we launched the ERUA Open Science Ambassador Programme. In this programme, four researchers working at different universities of the alliance took on the role as Open Science ambassadors. This paper illuminates the programme’s aims and discusses the risks we faced. It outlines how we got the programme going, explaining how we recruited our ambassadors, how we connected them, what knowledge and materials we equipped them with and how we communicated the programme within the alliance. Furthermore, the paper delineates the ambassadors’ activities, giving recommendations based on the challenges we encountered and the experiences we made. The paper is a valuable source of information for institutions that consider setting up similar Open Science ambassador programmes.